(untitled) (World Bulletin of Social Sciences, 2021)
This article examines the skill of teachers’ self-development as a criterion for increasing professional competence. The article also examines the psychological qualities of a successful teacher, professional competencies that contribute to the achievement of results in pedagogical activities, the sociopsychological aspects of self-development of future teachers, the social activity of the teacher and the ability to effectively organize the educational process.